Pretreatment Serum Lactate Dehydrogenase and Metastases Numbers as Potential Determinants of Anti-PD-1 Therapy Outcome in Nasopharyngeal Carcinoma - Wael A. S. Ali MD, PhD; Xinxin Huang MD; Yuehan Wu MD; Yuxiang Ma MD, PhD; Hui Pan MD, PhD; Jun Liao MD; Zhang Yang MD; Shaodong Hong MD, PhD; Yunpeng Yang MD, PhD; Yan Huang MD, PhD; Yuanyuan Zhao MD, PhD; Wenfeng Fang MD, PhD; et al. (Cancer Control, 2023)
Background We aimed to investigate the determinant factors of anti-PD-1 therapy outcome in nasopharyngeal carcinoma (NPC). Methods In this retrospective study, we included 64 patients with recurrent/metastatic NPC. The association of patients’ characteristics, C-reactive protein (CRP), neutrophil to lymphocyte ratio (NLR), and lactate dehydrogenase (LDH) with survival benefit of anti-PD-1 therapy were analyzed using Cox regression models and Kaplan-Meier analyses. Patients were divided based on the median value of CRP, NLR or LDH into different subgroups. Results At a median follow-up time of 11.4 months (range: 1-28 months), median progression-free survival (PFS) and overall survival (OS) were 1.9 months (95% CI, .18-3.6) and 15 months (95% CI, 10.9-19.1) months, respectively. Pretreatment metastases numbers was significant predictor of PFS (HR = 1.99; 95% CI 1.10-3.63; P = .024) and OS (HR = 2.77; 95% CI 1.36-5.61; P = .005). Baseline LDH level was independent predictor of OS (HR = 7.01; 95% CI 3.09-15.88; P < .001). Patients with LDH level >435 U/L at the baseline had significantly shorter PFS and OS compared to patients with LDH level ≤435 U/L (median PFS: 1.7 vs 3.5 months, P = .040; median OS: 3.7 vs 18.5 months, P < .001). Patients with non-durable clinical benefit (NDB) had significantly higher LDH level at the baseline compared to patients who achieved durable clinical benefit (DCB) ( P = .025). Post-treatment levels of CRP, LDH, and NLR were decreased compared to baseline in patients with DCB ( P = .030, P = .088, and P = .066, respectively), whereas, there was a significant increase in post-treatment level of LDH compared with baseline in patients with NDB ( P = .024). Conclusions LDH level at the baseline was an independent predictor of OS and pretreatment metastases numbers was a significant predictor of PFS and OS.